ChemInform Abstract: Catalytic Asymmetric Synthesis of (S)‐Laudanosine by Hydroamination. Issue 18 (11th April 2013) - Ogata, Tokutaro; Kimachi, Tetsutaro; Yamada, Ken‐ichi; Yamamoto, Yasutomo; Tomioka, Kiyoshi
Abstract Isoquinoline alkaloid laudanosine (VIII) and several analogues are prepared by hydroamination of corresponding aminoalkenes.